2018
DOI: 10.1007/jhep10(2018)004
|View full text |Cite
|
Sign up to set email alerts
|

Proof of the weak gravity conjecture from black hole entropy

Abstract: We prove that higher-dimension operators contribute positively to the entropy of a thermodynamically stable black hole at fixed mass and charge. Our results apply whenever the dominant corrections originate at tree level from quantum field theoretic dynamics. More generally, positivity of the entropy shift is equivalent to a certain inequality relating the free energies of black holes. These entropy inequalities mandate new positivity bounds on the coefficients of higher-dimension operators. One of these condi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
301
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(317 citation statements)
references
References 58 publications
14
301
2
Order By: Relevance
“…A similar idea was also suggested in [6]. This line of reasoning was applied to the case of a single U (1) charge Q in [4], where higher-derivative corrections to the classical entropy and extremality bound were computed explicitly and found to obey…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A similar idea was also suggested in [6]. This line of reasoning was applied to the case of a single U (1) charge Q in [4], where higher-derivative corrections to the classical entropy and extremality bound were computed explicitly and found to obey…”
Section: Introductionmentioning
confidence: 79%
“…This statement is the generalization of having an increased Q/M ratio in the case of multiple non-trivial quantum numbers. Hence, if the ∆S > 0 conjecture of [4] is correct, (3) proves that the extremality curves of a wide class of black hole systems display WGC-like behavior.…”
Section: Introductionmentioning
confidence: 94%
“…We have found that the entropy shift is always positive for this family of solutions. In previous works in the literature, it has been claimed that the positivity of the corrections to the entropy imply a positive correction to the charge-to-mass ratio at extremality [31][32][33]. On the contrary, this claim has been disputed by the counterexample presented in Ref.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, not all the solutions of the Einstein-Maxwell theory can be embedded in the Heterotic Superstring effective action because unequal electric and magnetic charges always generate a non-trivial scalar field. quantum black hole physics is currently attracting much attention [19,34,35,31,36,37,32,20,33,38]. A recurrent assumption in these explorations is that no additional degrees of freedom are activated at higher orders.…”
Section: Discussionmentioning
confidence: 99%
“…The difference with the results in Refs. [21][22][23] can be understood if one takes into account two facts. First of all, topological terms such as the Gauss-Bonnet invariant -which implicitly appears in the heterotic string effective action -modify the black hole entropy while keeping the solution unchanged.…”
Section: Discussionmentioning
confidence: 99%